2008
DOI: 10.1111/j.1600-0420.2007.00990.x
|View full text |Cite
|
Sign up to set email alerts
|

Fuchs' heterochromic uveitis: a longitudinal clinical study

Abstract: ABSTRACT.Purpose: To carry out a longitudinal study of patients with Fuchs' heterochromic uveitis (FHU) in western Sweden and to establish the factors responsible for diagnostic delay. Methods: A sample of 54 patients, 51 with monocular and three with binocular FHU, were followed for periods ranging from 8 months to 15 years. Firm diagnostic criteria were set. A detailed anamnesis regarding ocular and extraocular symptoms was taken. The eyes were repeatedly examined. Toxoplasma serology was analysed. Complicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
48
1
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 20 publications
6
48
1
3
Order By: Relevance
“…It is observed in about 2-3% of all patients in large uveitis surveys. 6,20,21 Infectious causes of FHUS have long been suspected. An American study reported that Toxoplasma gondii was involved in the pathogenesis of FHUS.…”
Section: Discussionmentioning
confidence: 99%
“…It is observed in about 2-3% of all patients in large uveitis surveys. 6,20,21 Infectious causes of FHUS have long been suspected. An American study reported that Toxoplasma gondii was involved in the pathogenesis of FHUS.…”
Section: Discussionmentioning
confidence: 99%
“…The mean interval between the first visit to an ophthalmologist and diagnosis is 3 years (up to 26 years), 21 but there are several reasons why diagnosis of FHI is often delayed. Keratic precipitates are not always stellate and diffuse.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with brown irides, the heterochromia can be subtle or absent, as both anterior and posterior layers have similar pigmentation and texture. 25,26 Although clinic-based studies from North America 22,25 and Europe 16,14,[27][28][29] have reported anywhere from 70.4% to 100% heterochromia in patients with FUS, similar studies from Brazil, 16 Mexico, 30 Turkey, 31 and China 15 reported heterochromia rates of 34%, 25.3%, 39.7%, and 12.7%, respectively. Iris atrophy, in contrast, was present in 53.3% of Mexican patients, 30 88.4% of Turkish patients, 31 and 100% of Chinese patients.…”
mentioning
confidence: 87%